COMPANY LIFE CYCLE INFLUENCE ON THE RESULTS OF THE INTEGRATION - M. Katalkina (Вестник университета)
The article presents the results of 47 mergers and acquisitions research. In the scope of the research the author analyzed the life cycle stages of the reorganized companies, the goals of mergers and acquisitions, changes of profit, stock price and dividends of the reorganized companies before and after integration. The results of the research allow to conclude that the most appropriate stages for integration are «youth» and «maturity». When planning the integration process it is necessary to consider life cycle stages of the participating companies, as they have a significant impact on the result of the integration.